EKSPERIMEN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS BERDASARKAN GENDER DI SDN 68 PALEMBANG - Ni Nyoman Revi Widhiyani; Nila Kesumawati; Endie Riyoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is all the knowledge of learning that occurs throughout human life bygiving a positive influence on every growth of a persons learning. The ProblemBased Learning model is one of the learning models that focuses on problem-solving skills in learning using real problems from everyday life to help studentslearn. Therefore, with the use of this Problem Based Learning model, it canimprove students critical mathematical thinking skills in learning. The purpose ofthis study aims to determine the effect of the problem based learning model oncritical mathematical thinking skills based on gender in elementary schools inPalembang. The method used in this study is an experimental method with a post-test design - only control group design. The population in this study were 62students in grade IV of SDN 68 Palembang, study, for the sample of this study 21students in grade IV A as experimental class and 21 students in grade IV B as thecontrol class without. Thr data collection technique in this study was a descriptivetest to measure student critical mathematical thinking skills. The data analysistechnique for this study used a two-way ANOVA test which showed that (1) therewas an effect of the problem based learning model on students criticalmathematical thinking skills; (2) there is a difference in the average mathematicalcritical thinking ability based on student gender: (3) there is an interaction betweenthe problem based learning model and gender on students mathematical criticalthinking ability.